2014
DOI: 10.1002/star.201300202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol and storage relative humidity on the properties of kudzu starch‐based edible films

Abstract: Kudzu (Pueraria lobata) starch films were prepared using glycerol as plasticizer. The effects of glycerol (0,10,20,30, and 40% of dry starch) and storage relative humidity (RH, 53, 75, and 100%) on molecular interactions, crystalline structural characterizations, and thermal stabilities of the films were investigated using Fourier transform-infrared (FT-IR) spectra, XRD, and thermogravimetry and DTA (TG-DTA). The results showed that kudzu starch could form intermolecular hydrogen bonds with glycerol and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
8
26
2
Order By: Relevance
“…As observed, the unplasticized SPS film shows a large amorphous area with crystalline peaks Fig. 7 Zhong and Li (2014) who suggested that peak 2θ at 17°e xhibited the formation of double-helical B-type crystalline. The X-ray diffraction patterns of unplasticized SPS films are similar to that of films containing glycerol (G-and GSplasticized films).…”
Section: Film Crystallinitymentioning
confidence: 65%
See 1 more Smart Citation
“…As observed, the unplasticized SPS film shows a large amorphous area with crystalline peaks Fig. 7 Zhong and Li (2014) who suggested that peak 2θ at 17°e xhibited the formation of double-helical B-type crystalline. The X-ray diffraction patterns of unplasticized SPS films are similar to that of films containing glycerol (G-and GSplasticized films).…”
Section: Film Crystallinitymentioning
confidence: 65%
“…Furthermore, it can be seen that the intensity of diffraction peaks increased as glycerol concentration increased from 0 to 45 % for G-and GS-plasticized films. Zhong and Li (2014) who studied the effect of glycerol on the properties of Kudzu starch films found that crystallinity of the films was enhanced as glycerol concentration increased from 0 to 40 %. Bergo et al (2008) also reported similar results regarding the crystallinity of cassava starch films with glycerol content from 0 to 45 %.…”
Section: Film Crystallinitymentioning
confidence: 99%
“…The higher glycerol-containing extruded material takes up more water during storage. Therefore, increases the rate of retrogradation [19].…”
Section: -3mentioning
confidence: 99%
“…Thus, starch has attracted a great deal of interest as a potential alternative to conventional plastics for packaging applications. Several studies have investigated the development and characterization of starch based films from corn [4,[6][7][8], potato [9][10][11][12][13], cassava [14][15][16][17][18][19][20], banana [21], yam [22,23], pea [1], sago [24][25][26], rice [27][28][29][30], maize [31][32][33][34], Kudzu [35] and agar [36][37][38][39]. According to Sahari et al [40] sugar palm starch is also a potential biopolymer material for making biodegradable films.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the addition of plasticizers decreases film mechanical resistance. The type and concentration of plasticizer employed has significant effect on the physical, thermal, mechanical and barrier properties of films [35,[50][51][52]. The most common plasticizer utilized for starch based films are polyols such as glycerol and sorbitol, amongst many others.…”
Section: Introductionmentioning
confidence: 99%